2018
DOI: 10.1089/thy.2018.0234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Excess Iodine Intake from Iodized Salt and/or Groundwater Iodine on Thyroid Function in Nonpregnant and Pregnant Women, Infants, and Children: A Multicenter Study in East Africa

Abstract: Although iodine intake was excessive and Tg concentrations were elevated, there was little impact on thyroid function. Chronic excess iodine intake thus appears to be well tolerated by women, infants, and children. However, such high iodine intake is unnecessary and should be avoided. Careful evaluation of contributions from both iodized salt and groundwater iodine is recommended before any review of iodization policy is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 58 publications
1
62
2
Order By: Relevance
“…At a salt intake of about 10 g/day, WHO recommends salt fortification at 20−40 mg/kg, and iodization of ≥15 mg/kg at consumption is adequate to prevent population iodine deficiency but not the risk of excess intakes in vulnerable groups . The risk of localized excess iodine intakes may increase if legislation stipulates salt iodine fortification above the recommended level or if salt is overiodized at production . Salt fortification should be adapted to the actual salt intake and the cumulative coverage of iodized salt, including coverage in staple processed foods, such as bread or bouillon …”
Section: Potential Sources Of Excessive Iodine Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…At a salt intake of about 10 g/day, WHO recommends salt fortification at 20−40 mg/kg, and iodization of ≥15 mg/kg at consumption is adequate to prevent population iodine deficiency but not the risk of excess intakes in vulnerable groups . The risk of localized excess iodine intakes may increase if legislation stipulates salt iodine fortification above the recommended level or if salt is overiodized at production . Salt fortification should be adapted to the actual salt intake and the cumulative coverage of iodized salt, including coverage in staple processed foods, such as bread or bouillon …”
Section: Potential Sources Of Excessive Iodine Exposurementioning
confidence: 99%
“…In iodine‐sufficient populations, if iodine intake is borderline, iodine is preferentially partitioned into breast milk to safeguard infant requirements . High breast milk iodine concentration (BMIC) is reported in areas with excess iodine intakes . Whether there is an active downregulation of iodine secretion into breast milk at elevated maternal iodine intakes remains unclear.…”
Section: Potential Sources Of Excessive Iodine Exposurementioning
confidence: 99%
“…The poor quality control could rather lead to nonuniform mixing during fortification procedures, leaving portions of salt with high fortificant concentrations. However, consumers are likely to be exposed to biological risks if exposed over a longer duration . The test kits used for the assessment of the iodine content of salt provided results in ranges.…”
Section: Discussionmentioning
confidence: 99%
“…A Danish study mapped different drinking water sources and found a wide variation of total iodine content . Similarly, a study in East Africa found high levels of iodine (≥10 μg/L) in 9% of drinking water samples . Thus, water mapping is critical in the assessment of total iodine intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation